Potential cardioprotective peptides generated in Spanish dry-cured ham - Marta Gallego; Leticia Mora; Fidel Toldrá (Journal of Food Bioactives, 2019)
Food-derived bioactive peptides are promising compounds for the prevention and treatment of cardiovascular diseases, the main cause of mortality in developed countries. The aim of this work was to determine the in vitro anti-inflammatory, antioxidant, and angiotensin I-converting enzyme (ACE-I) inhibitory activities of twenty-four peptides that were identified in Spanish dry-cured hams. For the first time, some peptides such as PSNPP, HCNKKYRSEM and FNMPLTIRITPGSKA showed anti-inflammatory activity expressed as platelet-activating factor-acetylhydrolase, autotaxin, and lipoxygenase inhibition. Peptides MDPKYR and TKYRVP were the strongest antioxidants, whereas GGVPGG, TKYRVP, and HCNKKYRSEM showed the highest ACE-I inhibitory activity. Additionally, several peptides such as KPVAAP, MDPKYR, TKYRVP, and HCNKKYRSEM exerted more than one of the assayed activities, increasing their health-enhancing potential. More studies are needed to evaluate the bioavailability of such peptides and their in vivo effect. This would contribute to consider dry-cured ham as a source of peptides beneficial for cardiovascular health.